WORK OF COMBINED LARGE DIAMETER PIPE (SLURRY PIPELINE) ON ALLUVIAL SOILS TAILING HGF - Hurzhij, A. O. (Science and Transport Progress, 2010)
The research results of influence of the deformation of tailing-dump dams on the sludge lines are considered. In designing the routes of sludge lines, it is offered to calculate the base deformations under the sludge line to substantiate the anti-destruction protection of sludge lines.